1970
DOI: 10.1111/j.1471-0528.1970.tb03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Caesarean Section

Abstract: Use of a ten degree left-side-down "tilt" position for Caesarean section has resulted in a very significant improvement in the oxygen saturation of umbilical artery and vein blood of infants at birth. This is especially notable in infants delivered from mothers under spinal block. It is believed that this improvement in the oxygenation of the fetus is due to release of pressure on the mother's vena cava which causes an increase in her cardiac output and improved perfusion of the uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…On the other hand Bromage (1975) stated that during the second stage of labour foetal pH fell by 0•26 over 30 minutes in the dorsal position but not in the lateral position. Ansari et al (1970) reported a significant improvement in umbilical vessel oxygen saturation at Caesarian Section when a ten degree left tilt was instituted, especially in patients under spinal block. Ueland et al (1968) found a 34% fall in cardiac output after subarachnoid block in the supine position prior to Caesarian Section.…”
Section: Stagnant Hypoxiamentioning
confidence: 95%
“…On the other hand Bromage (1975) stated that during the second stage of labour foetal pH fell by 0•26 over 30 minutes in the dorsal position but not in the lateral position. Ansari et al (1970) reported a significant improvement in umbilical vessel oxygen saturation at Caesarian Section when a ten degree left tilt was instituted, especially in patients under spinal block. Ueland et al (1968) found a 34% fall in cardiac output after subarachnoid block in the supine position prior to Caesarian Section.…”
Section: Stagnant Hypoxiamentioning
confidence: 95%
“…In this respect, our results confirm the findings of Ansari et a1. 28 and CrawfordZ4 who used the lateral tilt during general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The supine position has also been considered harmful to the fetus, especially during extradural block (Crawford, Burton and Davies, 1972). 0007-0912/79/080767-07 $01.00 anaesthesia (Ansari et al, 1970;Crawford, Burton and Davies, 1972;Downing et al, 1974), but there is still little direct evidence of a harmful effect of the maternal supine position on the fetus during extradural block for vaginal delivery.…”
mentioning
confidence: 99%